PENDIDIKAN AGAMA ANAK USIA DINI DALAM PENGASUHAN ETNIS JAWA DAN MELAYU DI TK ALFIA NUR HAMPARAN PERAK - Rahman, Mhd. Habibu; Arifa Lubis, Sofni Indah; Anggraini, Dwi (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
Religious education needs to be introduced and instilled in children from an early age as an effort to form a spiritually strong generation. In fact, every human being is born with the potential for spiritual intelligence. The potential that every child has will develop rapidly if they get care that is appropriate to the child's development. The fact is that every ethnicity has different characteristics and parenting styles. For example, the Javanese and Malay ethnic groups, each of which has its own way of instilling religious values in children from an early age. The purpose of this study was to determine the form of early childhood religious education in the care of Javanese and Malay ethnicity in TK Alfia Nur Hamparan Perak. The method used in this research is a qualitative research method. Data collection techniques were carried out by means of observation and interviews. All existing data were analyzed by means of data condensation, data display and verification stages. The results of this study indicate that the form of instilling religious values in early childhood in the upbringing of Javanese and Malay ethnicities uses storytelling, example and habituation methods, furthermore ethnic characteristics in parents influence parenting style and have implications for the form of instilling religious values in early childhood. Therefore, the parenting culture that parents receive should not be purely applied to children, nor should it be completely abandoned.